The Influence of The Principle's Leadership Style and Achievement Motivation on Teachers' Work Effectiveness - Ahmad Karim; Saima Rambe; Saipul Bahri Harahap; Bobi Indra Prayoga (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
Principal leadership has an important role in running educational institutions. The principal is not only a manager but also a role model for members of the organization through a good leadership model or style. This research looks for gaps in previous research that have not been researched. Apart from that, this research aims to find out and analyze the influence of leadership style on teacher work effectiveness, secondly, analyze the influence of achievement motivation on teacher work effectiveness and analyze the principal's leadership style and achievement motivation on effectiveness. teacher work simultaneously. This type of research is quantitative research with a survey method with a population and sample of 33 people, in selecting the sample using non-probability sampling with the census method. The data used is primary data obtained through questionnaires which were distributed and filled in directly by the respondents and it was obtained that partial and simultaneous research results showed that leadership style and achievement motivation had a positive and significant influence on teacher work effectiveness.